Micro, Small and Medium Enterprises (SMEs) and Great Opportunities to Return After the Covid Pandemic in Makassar City - St. Rukaiyah; Hapsawati Taan; Sultan Sultan; Hasniaty Hasniaty (Universitas Dharma Wacana, 2022)
This study aims to find out the strategies used to bounce back after the Covid-19 pandemic carried out by MSME players in the city of Makassar. This study uses a qualitative descriptive analysis and uses a SWOT analysis, namely Strengths, Weaknesses, Opportunities and Threats. SWOT analysis is an analysis used to evaluate strengths and weaknesses in the internal environment and evaluate opportunities and threats in the external environment of MSMEs. The results of this study indicate that the total IFAS score is 3.57 which indicates a good internal position and the total EFAS score is 3.44 which indicates a moderate external position. This position indicates that MSMEs are increasingly strategic even though they still face quite tough challenges. Based on the results of the SWOT matrix analysis, the strategy adopted is as follows: maintaining customer trust by improving the quality and quality of the food menu and forming a reliable sales team that prioritizes service so that they can compete.